1994
DOI: 10.1007/bf01857953
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a home-based intervention program to reduce infant passive smoking and lower respiratory illness

Abstract: We conducted a randomized controlled trial to determine whether a home-based intervention program could reduce infant passive smoking and lower respiratory illness. The intervention consisted of four nurse home visits during the first 6 months of life, designed to assist families to reduce the infant's exposure to tobacco smoke. Among the 121 infants of smoking mothers who completed the study, there was a significant difference in trend over the year between the intervention and the control groups in the amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
1
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 25 publications
6
91
1
1
Order By: Relevance
“…Of these, 403 articles concerned topics not relevant to this study, and 18 met the inclusion criteria for this review. 13,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] The trials were conducted in the United States, China, Norway, Scotland, Finland, Italy, and Australia between 1987 and 2010. Forty-seven studies were excluded for the following reasons: quit rates were not reported or were not reported separately for intervention and control groups, or numbers of participants were not reported (24 studies ; the study design was not a controlled trial [11 studies [59][60][61][62][63][64][65][66][67][68][69] ]), the interventions were not aimed at parents of young children (9 studies [70][71][72][73][74][75][76][77][78] ); the reporting period was less than 1 month (1 study 79 ); a protocol only was reported (1 study 80 ); the report was not in English (1 study 81 ).…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 403 articles concerned topics not relevant to this study, and 18 met the inclusion criteria for this review. 13,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] The trials were conducted in the United States, China, Norway, Scotland, Finland, Italy, and Australia between 1987 and 2010. Forty-seven studies were excluded for the following reasons: quit rates were not reported or were not reported separately for intervention and control groups, or numbers of participants were not reported (24 studies ; the study design was not a controlled trial [11 studies [59][60][61][62][63][64][65][66][67][68][69] ]), the interventions were not aimed at parents of young children (9 studies [70][71][72][73][74][75][76][77][78] ); the reporting period was less than 1 month (1 study 79 ); a protocol only was reported (1 study 80 ); the report was not in English (1 study 81 ).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Interventions included some of the following components: self-help materials (12 studies 13,18,[20][21][22]24,26,[29][30][31]33,34 ), face-toface counseling (16 studies [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] ), telephone counseling (6 studies 13,[18][19][20]32,34 ), cessation medications (2 studies 24,28 ), and cotinine feedback (1 study 32,39 20,24,32 ).…”
Section: Intervention Componentsmentioning
confidence: 99%
“…In a study by Greenberg et al, 38 nurses made four 45-minute home visits over a 6-month period to treatment group mothers. Visits included education about ETS and the detrimental health effects, identification of sources of ETS, development of a plan to reduce ETS exposure, and reinforcement for steps taken toward ETS reduction.…”
Section: Reducing Ets Exposure Health Effects Of Ets On Childrenmentioning
confidence: 99%
“…Public education has been used to increase awareness of the dangers of SHSe on health consequences, and legislation has been used for controlling smoking in public places (World Health Organization, 2013). Smoking in the home cannot be prohibited by law, however it has been shown that one way to reduce SHSe is by promotion of a smoke-free home (SFH) (Greenberg et al, 1994). The effectiveness of education programs for a SFH vary depending on the intervention strategy, population, setting, and health conditions of the target population (Gehrman and Hovell, 2003).…”
Section: Introductionmentioning
confidence: 99%